Pengembangan Instrumen Tes Keterampilan Teknik Sepakbola untuk Pemain U-17 - Afrizal S; Vega Soniawan (Jurnal Patriot, 2021)
To find out the technical ability of football for U-17 football players, a precise and permanent test is needed. However, in the field, the forms used by the teaching staff and trainers who use standardized tests or those that already have standards have not been maximized to measure the skill level. The population of this study was 103 people in the U-17 group, which were taken from officially registered football coaching at the PSSI Padang City Association (Askot) and the Padang City SSB League Agency who were still active. Data were collected by implementing passing tests, long passing tests, shooting tests and heading tests. The data analysis technique uses the product moment correlation technique to find validity and reliability using the alpha correlation coefficient formula. To determine the football technique scoring norms, use the Scale 5 formula. Based on the results of data analysis obtained; (1) Level of validity: the passing test is 0.53 (moderate), the long passing test is 0.50 (moderate), the shooting test is 0.53 (moderate) and the heading test is 0.53 (moderate). (2) Reliability level: passing test of 0.194 (acceptable), long passing test of 0.174 (acceptable), shooting test of 0.368 (acceptable) and heading test of 0.014 (unacceptable).